Management of blunt trauma abdomen in a tertiary care teaching hospital: a surgical audit - H. B., Shashikumar; B. S., Madhu; Sebastian, Ajo (International Surgery Journal, 2018)
Background: Blunt abdominal trauma is a common scenario in Emergency department and the common cause being road traffic accidents. With this study we present our experience with blunt trauma of abdominal solid organ injuries over a period of 12 months. Methods: A retrospective study was conducted among 45 blunt trauma of abdominal solid organ injuries who presented to the emergency room of Department of General Surgery of Mysore Medical College and Research Institute, Mysore from 1st January 17 to 31st December 2017.All date were retrieved from medical records and statistical analysis was performed using Epi info version 7. Results: Mean age of study population was 31.46 years. 78.2% of the patients were males. Thirty-three (73.3%) patients undergone non-operative management. Splenic injury was reported as the most common abdominal solid organ injury followed by liver. Conclusions: With the advent of newer investigative modalities like contrast enhanced computed tomography (CECT) abdomen, more and more cases of blunt trauma abdominal solid organ injury can be managed non-operatively with effective ICU care. High-grade injuries do not preclude non-operative management.